Peningkatan kualitas pembelajaran matakuliah proses permesinan 3 dengan penerapan "Self Assessment" - Wagiran, Wagiran (Jurnal Cakrawala Pendidikan, 2016)
Ths article concerns a research aimed at improving the quality of learning using self-assessment in the class of Machining Process 3 with the improvement indicated by the students activeness in learning followed by improvement in their performance. The research was a classroom action research consisting of three cycles and conducted on 15 students taking the Machanial Engineering Course PRogram. The data were collated through observation and self-assessment. Then they ware analyzed qualitatively and descriptively. The result indicates that implementation of self-assessment can improve students activeness in learning as well as enhance hhier learning performance. It is suggested that self-assessment be implemented in a class of a larger group of students